This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Thank you, long solution but really simple
Nice solution!
Define, f ( n ) = ⌊ 2 n ⌋ + ⌊ 3 n ⌋ + ⌊ 6 n ⌋ g ( n ) = f ( n ) − ( n − 1 ) ⟹ f ( n + 6 ) = f ( n ) + 6 ⟹ g ( n + 6 ) = g ( n )
So, if g ( n ) = 0 ⟹ g ( n + 6 k ) = 0 ∀ k ∈ Z .
Now, note that g ( 1 ) = g ( 2 ) = g ( 3 ) = g ( 4 ) = 0 g ( 5 ) = 0 g ( 6 ) = 0 g ( n ) = 0 ⟹ n ≡ k ( m o d 6 ) k = 1 , 2 , 3 , 4
Hence, the number of required solutions is 6 8 .
Essentially the same idea as Peter's. I must appreciate the way your solution has been written. Compact and clear!
We know that every integer can be written in form of 6 κ + ψ . Where
κ ∈ N and
0 ≤ ψ ≤ 5 , ψ is also a natural number.
Now
∀ s u c h κ , ψ = 0 , 5 does not satisfies. Hence 32 solutions are to be emitted from o n e hundred.
Hence answer is 6 8 .
Via induction one can recognize that among the 100 possible values for n always 2 in equidistance must be removed resp.:
n k = 5 + 6 k ; n k + 1 = 6 ( k + 1 ) with 0<=k<=15)
As result there are 100 - 2*16 =68 solutions.
Problem Loading...
Note Loading...
Set Loading...
Each integer n can be written as n = 6 k + p where k and p are integers and 0 ≤ p ≤ 5 .
Now for each value of p the left hand side of the equation can be evaluated term by term to get
For p = 0, n = 6 k and the left hand side becomes
( 3 k ) + ( 2 k ) + ( k ) = 6 k = n − 1 and so n = 6 k is NOT a solution of the equation.
For p = 1, n = 6 k + 1 and the left hand side becomes
( 3 k ) + ( 2 k ) + ( k ) = 6 k = n − 1 and so n = 6 k + 1 is a solution of the equation.
For p = 2, n = 6 k + 2 and the left hand side becomes
( 3 k + 1 ) + ( 2 k ) + ( k ) = 6 k + 1 = n − 1 and so n = 6 k + 2 is a solution of the equation.
For p = 3, n = 6 k + 3 and the left hand side becomes
( 3 k + 1 ) + ( 2 k + 1 ) + ( k ) = 6 k + 2 = n − 1 and so n = 6 k + 3 is a solution of the equation.
For p = 4, n = 6 k + 4 and the left hand side becomes
( 3 k + 2 ) + ( 2 k + 1 ) + ( k ) = 6 k + 3 = n − 1 and so n = 6 k + 4 is a solution of the equation.
For p = 5, n = 6 k + 5 and the left hand side becomes
( 3 k + 2 ) + ( 2 k + 1 ) + ( k ) = 6 k + 3 = n − 1 and so n = 6 k + 5 is NOT a solution of the equation.
By examining the above cases we see that the equation fails to have a solution whenever n is a multiple of 6 or one less than a multiple of six. So for n between 1 and 100 the number of failures is
2 × ⌊ 6 1 0 0 ⌋ = 3 2
and so the number of successes is
1 0 0 − 3 2 = 6 8